To collaborate or not? The moderating effects of team conflict on performance‐prove goal orientation, collaboration, and team performance. Issue 3 (2nd July 2021) - E. Downes, Patrick; Gonzalez‐Mulé, Erik; Seong, Jee Young; Park, Won‐Woo
Abstract : This study examines the effect of team performance‐prove goal orientation on team collaboration and team performance by identifying team conflict as a boundary condition. We propose that team conflict plays a moderating role such that high‐PPGO team members will work collaboratively when they experience task conflict because they perceive other team members to be valuable for team performance. In contrast, high‐PPGO teams will be less likely to work collaboratively when they experience relationship conflict since interpersonal differences will be salient, forcing social comparisons to which high‐PPGO team members are predisposed. We test our hypotheses in a field sample of 485 working teams (2, 940 individuals). The result shows that team PPGO was positively related to collaboration and team performance under conditions of high task conflict (and low relationship conflict). In contrast, team PPGO was negatively related to collaboration and team performance under conditions of high relationship (and low task) conflict. Team PPGO showed no relationship with collaboration when both task and relationship conflict were either high or low. These results extend knowledge of the multi‐faceted effects of team PPGO and represent the first study showing the differential effect of PPGO on team collaborative processes. Implications for future research and practices are discussed. Practitioner points: Performance‐prove goal orientation (PPGO) improves team collaboration when task conflict is high and relationship conflict is low, while PPGO harms team collaboration when task conflict is low and relationship conflict is high. Organizations should stimulate task conflict, and reduce relationship conflict, in teams with a greater degree of high PPGO members to ensure collaboration and high performance. Otherwise, high PPGO teams will be unlikely to collaborate as members may view each other as rivals.